Faktor – Faktor yang Mempengaruhi Keputusan Pembelian pada UMKM Makanan Batam - Paramitha Tanujaya, Priscillia; Budiman, Johny (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted to determine the influence of brand image, digital marketing, price, product quality, trust, and product quality through trust on purchasing decisions. The research method used was a quantitative method using as many as 310 respondents from Batam City residents who had purchased food from small and medium enterprises in Batam with research results that brand image, digital marketing, service quality, product quality, and trust had a positive influence on purchasing decisions. Meanwhile, the price variable has no positive influence on purchasing decisions. and product quality mediated by trust has a significant influence on purchasing decisions.